Ceramic composition, ceramic substrate, preparation method and application thereof
By adding BaxSr1-xTiO3, glass phase and rare earth oxides to the alumina ceramic substrate, the problems of low dielectric constant, high dielectric loss and insufficient breakdown strength are solved, and a ceramic substrate with high dielectric constant, low dielectric loss, high breakdown strength and high density are achieved.
Patent Information
- Application Number
- CN202310391589.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-13
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-04-13
AI Technical Summary
In the application of high-frequency circuits, existing alumina ceramic substrates have low dielectric constant, high dielectric loss, and insufficient breakdown strength, making it difficult to meet the requirements of high-frequency signal transmission.
Using ceramic compositions, including 97-99% alumina, 0.5-2% BaxSr1-xTiO3, 0.3-0.7% glass phase and 0.2-0.7% rare earth oxide, the dielectric properties are improved through the synergistic action of barium strontium titanate and alumina, the glass phase reduces the sintering temperature, and the rare earth oxide promotes grain growth and density increase.
The dielectric constant and breakdown strength of the ceramic substrate are significantly improved, the dielectric loss and sintering temperature are reduced, and the density and density of the material are improved.
Smart Images

Figure BDA0004175970520000111 
Figure BDA0004175970520000121 
Figure BDA0004175970520000122
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ceramic materials, and in particular relates to a ceramic composition, a ceramic substrate, and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid development of the 5G electronic communications market, electronic products are constantly developing in the direction of high integration, and the requirements for materials for high-frequency and high-speed signals are also increasing. When high-frequency signals pass through the dielectric layer, the molecules in the medium will try to orient themselves according to these electromagnetic signals. Although in fact the molecules in the medium are cross-linked and cannot be truly oriented, the change in frequency causes the molecules to move constantly, thereby generating a large amount of heat and causing energy loss. This loss is also called dielectric loss. The existence of dielectric loss will cause the temperature of electronic devices to rise, thereby reducing their service life and increasing production costs. Therefore, in the actual production process, the designed device must not only have a high dielectric constant ε r and breakdown strength E b , and at the same time have low dielectric loss tanδ.
[0003] Alumina ceramic substrates are widely used in high-frequency circuit substrates due to their good thermal conductivity, mechanical strength and dielectric properties. However, in the actual application development of high-frequency electronics, higher breakdown strength and lower dielectric loss are required to meet actual needs. Therefore, improving the dielectric constant, breakdown strength and reducing the dielectric loss of alumina ceramic substrates are of great significance in their application in high-frequency substrates.
[0004] At present, the main components of alumina ceramic substrates include 90-99% alumina and different contents of flux, dispersant and binder, etc. The dielectric constant and dielectric loss of ceramic substrates mainly depend on the intrinsic dielectric properties of the main crystalline phase alumina. The dielectric constant of alumina ceramics is usually between 9 and 10, the breakdown strength is about 18kV / mm, and the dielectric loss is less than 10. -4 However, it is very difficult to improve the intrinsic properties of the material. Therefore, in actual production, when only alumina powder is used as the single ceramic material in the substrate, it is difficult to achieve a significant improvement in the dielectric properties of the ceramic substrate, thus limiting its application in high-frequency circuit substrates. Summary of the invention
[0005] In order to overcome the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a ceramic composition, and a ceramic substrate made of the ceramic composition has a high dielectric constant, low dielectric loss, high breakdown strength and high density.
[0006] A second object of the present invention is to provide a ceramic substrate comprising the above ceramic composition.
[0007] A third object of the present invention is to provide a method for preparing the above-mentioned ceramic substrate.
[0008] A fourth object of the present invention is to provide an application of the above-mentioned ceramic composition or ceramic substrate in electronic devices.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] The first aspect of the present invention provides a ceramic composition comprising the following components in percentage by mass: 97-99% alumina, 0.5-2% Ba x Sr 1-x TiO3, 0.3-0.7% glass phase, 0.2-0.7% rare earth oxide; wherein x=0.3-0.5; the glass phase includes MgO, CaO and SiO2.
[0011] In the ceramic composition of the present invention, aluminum oxide is the main component, and after being prepared into a ceramic substrate, it is the main crystalline phase; barium strontium titanate (Ba x Sr 1-x TiO3) is the doping phase, and the dielectric properties of the ceramic substrate are improved through the synergistic effect of aluminum oxide and barium strontium titanate; the addition of the glass phase can reduce the sintering temperature of the ceramic; the addition of rare earth oxides promotes the growth of grains and the improvement of density during the sintering process.
[0012] Barium strontium titanate (Ba x Sr 1-x TiO3) is a complete solid solution of strontium titanate and barium titanate, with a typical perovskite structure. It has both the high dielectric constant of BaTiO3 (about 1400 at room temperature) and the low dielectric loss (about 0.012) and high breakdown strength of SrTiO3. x Sr 1-x Adding TiO3 into alumina ceramics can effectively improve its dielectric properties. x Sr 1-x TiO3 and alumina will generate TiO2. 4+ The radius (86 pm) is smaller than that of Al 3+ The radius (53 pm) is slightly larger, Ti 4+ Substitution of Al 3+ The lattice is deformed and defects are generated. These defects activate the lattice, reduce the activation energy of alumina ceramic sintering, and thus promote its sintering.
[0013] The dielectric constant and breakdown strength of ceramic substrates increase with the increase of Ba x Sr 1-xThe increase in the amount of TiO3 added shows a trend of first increasing and then decreasing. When the addition amount is low (less than 0.5%), it cannot effectively promote the density of the ceramic, and therefore cannot improve the dielectric properties of the ceramic; when the addition amount exceeds 2%, Ba x Sr 1-x TiO3 reacts with alumina to form a large number of second phases, which causes the overall dielectric constant of the ceramic to decrease; when Ba x Sr 1-x When the addition amount of TiO3 is about 1.5%, it can not only promote the densification of ceramics, but also will not produce much second phase, thereby effectively improving the dielectric constant and breakdown strength of the ceramic substrate.
[0014] The glass phase can produce a glass liquid phase during the sintering process. The liquid phase produces particle bonding and fills pores through surface tension, and can promote the migration of main crystal phase particles, inhibit the abnormal growth of alumina grains, and thus reduce the sintering temperature. In addition, the glass liquid phase located at the grain boundary hinders the migration of free charges. The free charges accumulate at the obstacles to form a macroscopic electric dipole moment, thereby improving the dielectric constant and breakdown strength of the ceramic.
[0015] When the amount of glass phase added is small, it cannot effectively form a liquid phase with alumina ceramics, thereby failing to effectively reduce the porosity of the ceramics and reduce the sintering temperature; when the amount of glass phase added is large, Ba x Sr 1-x The reduced content of TiO3 and rare earth oxides cannot effectively promote the liquid phase formation process between them and alumina ceramics, thereby failing to reduce the sintering temperature.
[0016] Rare earth oxides can promote the filling of pores in ceramics, reduce the porosity of alumina ceramics, refine the grains, and effectively improve the degree of densification and breakdown strength; rare earth oxides can also effectively promote the formation of low-melting liquid phases by components such as glass phases, thereby effectively reducing the melting point of ceramic substrate materials; in addition, rare earth oxides have a large ionic radius that prevents them from being dissolved in alumina, and they can hinder the migration of other ions (such as alkali metal oxides contained in alumina powder) at the grain boundaries, thereby reducing the dielectric loss of alumina ceramics.
[0017] When the addition amount of rare earth oxide is too low, it cannot effectively promote the formation of low-melting-point liquid phase by components such as glass phase, and thus cannot effectively reduce the melting point of the ceramic substrate material; when the addition amount is too high, it exists in large quantities on the grain boundaries of alumina ceramics, seriously hindering the migration rate of the grain boundaries and being unfavorable for the formation of a dense structure.
[0018] Preferably, in the ceramic composition, Ba x Sr 1-xTiO3 is prepared by a preparation method comprising the following steps: mixing BaTiO3 and SrTiO3, drying, and debinding to obtain the BaTiO3 x Sr 1-x TiO3.
[0019] Preferably, the Ba x Sr 1-x In the preparation method of TiO3, pulverization is performed after mixing; further preferably, the pulverization method is selected from ball milling; further preferably, the ball milling method is selected from wet ball milling.
[0020] Preferably, the Ba x Sr 1-x In the preparation method of TiO3, the ball milling time is 3 to 10 hours; further preferably, the Ba x Sr 1-x In the preparation method of TiO3, the ball milling time is 4 to 8 hours; more preferably, the Ba x Sr 1-x In the preparation method of TiO3, the ball milling time is 5 to 7 hours.
[0021] Preferably, the Ba x Sr 1-x In the preparation method of TiO3, the drying temperature is 70-140°C; further preferably, the Ba x Sr 1-x In the preparation method of TiO3, the drying temperature is 80-130°C; more preferably, the Ba x Sr 1-x In the preparation method of TiO3, the drying temperature is 90-120°C.
[0022] Preferably, the Ba x Sr 1-x In the preparation method of TiO3, the debinding temperature is 1100-1400°C; further preferably, the Ba x Sr 1-x In the preparation method of TiO3, the debinding temperature is 1200-1350°C; more preferably, the Ba x Sr 1-x In the preparation method of TiO3, the debinding temperature is 1250-1300°C.
[0023] Preferably, the Ba x Sr 1-x In the preparation method of TiO3, the debinding time is 3 to 6 hours; further preferably, the Ba x Sr 1-xIn the preparation method of TiO3, the debinding time is 3.5 to 5.5 hours; more preferably, the Ba x Sr 1-x In the preparation method of TiO3, the debinding time is 4 to 5 hours.
[0024] Preferably, in the ceramic composition, the rare earth oxide includes at least one of lanthanum oxide, neodymium oxide, dysprosium oxide, cerium oxide, yttrium oxide or erbium oxide; further preferably, in the ceramic composition, the rare earth oxide includes at least one of lanthanum oxide, neodymium oxide, dysprosium oxide, cerium oxide or yttrium oxide; even further preferably, in the ceramic composition, the rare earth oxide includes at least one of lanthanum oxide, neodymium oxide, dysprosium oxide or cerium oxide.
[0025] Preferably, in the ceramic composition, the average particle size of the rare earth oxide is 0.5 to 2 μm; further preferably, in the ceramic composition, the average particle size of the rare earth oxide is 0.8 to 1.8 μm; further preferably, in the ceramic composition, the average particle size of the rare earth oxide is 1 to 1.5 μm.
[0026] Preferably, in the glass phase, the mass ratio of MgO and CaO is 1:(0.7-1.3); further preferably, in the glass phase, the mass ratio of MgO and CaO is 1:(0.8-1.2); further preferably, in the glass phase, the mass ratio of MgO and CaO is 1:(0.85-1.15); more preferably, in the glass phase, the mass ratio of MgO and CaO is 1:(0.9-1.1).
[0027] Preferably, in the glass phase, the mass ratio of MgO and SiO2 is 1:(1.6-2.4); further preferably, in the glass phase, the mass ratio of MgO and SiO2 is 1:(1.7-2.3); further preferably, in the glass phase, the mass ratio of MgO and SiO2 is 1:(1.8-2.2); more preferably, in the glass phase, the mass ratio of MgO and SiO2 is 1:(1.9-2.1).
[0028] Preferably, in the glass phase, the mass ratio of MgO, CaO and SiO2 is 1: (0.7-1.3): (1.6-2.4); further preferably, in the glass phase, the mass ratio of MgO, CaO and SiO2 is 1: (0.8-1.2): (1.7-2.3); further preferably, in the glass phase, the mass ratio of MgO, CaO and SiO2 is 1: (0.85-1.15): (1.8-2.2); more preferably, in the glass phase, the mass ratio of MgO, CaO and SiO2 is 1: (0.9-1.1): (1.9-2.1).
[0029] Preferably, in the ceramic composition, the mass percentage of aluminum oxide is 97.1-98.5%; further preferably, in the ceramic composition, the mass percentage of aluminum oxide is 97.2-98%; further preferably, in the ceramic composition, the mass percentage of aluminum oxide is 97.4-97.8%.
[0030] Preferably, in the ceramic composition, Ba x Sr 1-x The mass percentage of TiO3 is 0.8-1.9%; further preferably, in the ceramic composition, Ba x Sr 1-x The mass percentage of TiO3 is 1.0-1.8%; more preferably, in the ceramic composition, Ba x Sr 1-x The mass percentage of TiO3 is 1.2-1.7%.
[0031] Preferably, in the ceramic composition, the mass percentage of the glass phase is 0.35-0.65%; further preferably, in the ceramic composition, the mass percentage of the glass phase is 0.4-0.6%; further preferably, in the ceramic composition, the mass percentage of the glass phase is 0.45-0.55%.
[0032] Preferably, in the ceramic composition, the mass percentage of rare earth oxide is 0.25-0.65%; further preferably, in the ceramic composition, the mass percentage of rare earth oxide is 0.3-0.6%; further preferably, in the ceramic composition, the mass percentage of rare earth oxide is 0.35-0.55%.
[0033] Preferably, the ceramic composition comprises the following components in mass percentage: 97.1-98.5% alumina, 0.8-1.9% Ba x Sr 1-x TiO3, 0.35-0.65% glass phase, 0.25-0.65% rare earth oxide.
[0034] Further preferably, the ceramic composition comprises the following components in mass percentage: 97.2-98% alumina, 1.0-1.8% Ba x Sr 1-x TiO3, 0.4-0.6% glass phase, 0.3-0.6% rare earth oxide.
[0035] More preferably, the ceramic composition comprises the following components in mass percentage: 97.4-97.8% alumina, 1.2-1.7% Ba x Sr 1-xTiO3, 0.35-0.55% glass phase, 0.35-0.55% rare earth oxide.
[0036] A second aspect of the present invention provides a ceramic substrate comprising the ceramic composition according to the first aspect of the present invention.
[0037] The third aspect of the present invention provides a method for preparing the ceramic substrate according to the second aspect of the present invention, comprising the following steps: x Sr 1-x TiO3, MgO, CaO, SiO2, rare earth oxide, dispersant and binder are mixed, cast and sintered to obtain the ceramic substrate.
[0038] Preferably, in the preparation method of the ceramic substrate, the dispersant includes at least one of oleic acid, triolein, fish oil or phosphate ester; further preferably, in the preparation method of the ceramic substrate, the dispersant includes at least one of oleic acid, triolein or phosphate ester; even further preferably, in the preparation method of the ceramic substrate, the dispersant includes oleic acid, phosphate ester or a combination thereof.
[0039] Preferably, in the preparation method of the ceramic substrate, the amount of the dispersant used is 0.1-3% of the mass of the ceramic composition; further preferably, in the preparation method of the ceramic substrate, the amount of the dispersant used is 0.3-2.5% of the mass of the ceramic composition; further preferably, in the preparation method of the ceramic substrate, the amount of the dispersant used is 0.5-2% of the mass of the ceramic composition.
[0040] Preferably, in the preparation method of the ceramic substrate, the binder includes at least one of polyvinyl butyral (PVB), acrylic resin, methyl cellulose, ethyl cellulose, nitrocellulose ester, polyurethane resin or phenolic resin; further preferably, in the preparation method of the ceramic substrate, the binder includes at least one of polyvinyl butyral (PVB), acrylic resin, methyl cellulose, ethyl cellulose or nitrocellulose ester; even more preferably, in the preparation method of the ceramic substrate, the binder includes at least one of polyvinyl butyral (PVB), acrylic resin or methyl cellulose.
[0041] Preferably, in the preparation method of the ceramic substrate, the amount of the binder used is 1 to 20% of the mass of the ceramic composition; further preferably, in the preparation method of the ceramic substrate, the amount of the binder used is 3 to 15% of the mass of the ceramic composition; further preferably, in the preparation method of the ceramic substrate, the amount of the binder used is 5 to 10% of the mass of the ceramic composition.
[0042] Preferably, in the method for preparing the ceramic substrate, pulverization is performed after mixing; further preferably, the pulverization method is selected from ball milling.
[0043] Preferably, in the preparation method of the ceramic substrate, the ball milling solvent is selected from an organic solvent; further preferably, the organic solvent includes toluene, isopropanol or a combination thereof; further preferably, the organic solvent includes toluene and isopropanol in a volume ratio of 1:(0.5-2); more preferably, the volume ratio of toluene and isopropanol is 1:(0.8-1.5).
[0044] Preferably, in the method for preparing the ceramic substrate, the ball milling medium is selected from alumina.
[0045] Preferably, in the preparation method of the ceramic substrate, the mass ratio of the ceramic composition to the ball milling medium is 1:(1-2); further preferably, in the preparation method of the ceramic substrate, the mass ratio of the ceramic composition to the ball milling medium is 1:(1.2-1.8); further preferably, in the preparation method of the ceramic substrate, the mass ratio of the ceramic composition to the ball milling medium is 1:(1.4-1.6).
[0046] Preferably, in the preparation method of the ceramic substrate, the ball milling time is 10 to 30 hours; further preferably, in the preparation method of the ceramic substrate, the ball milling time is 12 to 25 hours; further preferably, in the preparation method of the ceramic substrate, the ball milling time is 15 to 20 hours.
[0047] Preferably, in the method for preparing the ceramic substrate, degassing is performed before casting; further preferably, the degassing time is 5 to 10 hours; further preferably, the degassing time is 6 to 8 hours.
[0048] Preferably, in the method for preparing the ceramic substrate, debinding is performed before sintering.
[0049] In the preparation method of the ceramic substrate of the present invention, debinding is performed before sintering to discharge the binder and obtain a ceramic substrate with better performance.
[0050] Preferably, in the preparation method of the ceramic substrate, the debinding temperature is 250-400°C; further preferably, in the preparation method of the ceramic substrate, the debinding temperature is 280-380°C; further preferably, in the preparation method of the ceramic substrate, the debinding temperature is 300-350°C.
[0051] Preferably, in the preparation method of the ceramic substrate, the debinding time is 20 to 36 hours; further preferably, in the preparation method of the ceramic substrate, the debinding time is 22 to 34 hours; further preferably, in the preparation method of the ceramic substrate, the debinding time is 24 to 32 hours.
[0052] Preferably, in the preparation method of the ceramic substrate, the sintering temperature is 1400-1800°C; further preferably, in the preparation method of the ceramic substrate, the sintering temperature is 1500-1700°C; further preferably, in the preparation method of the ceramic substrate, the sintering temperature is 1550-1650°C.
[0053] Preferably, in the method for preparing the ceramic substrate, the sintering time is 15 to 30 hours; further preferably, in the method for preparing the ceramic substrate, the sintering time is 18 to 28 hours; further preferably, in the method for preparing the ceramic substrate, the sintering time is 20 to 25 hours.
[0054] The fourth aspect of the present invention provides a use of the ceramic composition described in the first aspect of the present invention or the ceramic substrate described in the second aspect of the present invention in an electronic device.
[0055] Preferably, the electronic device is a high-frequency electronic device; further preferably, the high-frequency electronic device is a high-frequency circuit substrate.
[0056] The beneficial effects of the present invention are as follows: the present invention provides a ceramic composition, which has the advantages of high dielectric constant, low dielectric loss, high breakdown strength and high density after being made into a ceramic substrate. In the ceramic composition of the present invention, aluminum oxide is the main component, and after being prepared into a ceramic substrate, it is the main crystalline phase; barium strontium titanate (Ba x Sr 1-x TiO3) is the doping phase, and the dielectric properties of the ceramic substrate are improved through the synergistic effect of aluminum oxide and barium strontium titanate; the addition of the glass phase can reduce the sintering temperature of the ceramic; the addition of rare earth oxides promotes the growth of grains and the improvement of density during the sintering process. DETAILED DESCRIPTION
[0057] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.
[0058] Example 1
[0059] The composition of the ceramic composition in this embodiment is as follows:
[0060] composition Alumina <![CDATA[Ba x Sr. 1-x TiO3]]> Glass Phase Rare Earth Oxides Mass percentage 97% 2% 0.3% 0.7%
[0061] Among them, Ba x Sr 1-x x in TiO3 is 0.4; the mass ratio of MgO:CaO:SiO2 in the glass phase is 1:1:2; the rare earth oxide is lanthanum oxide, and the average particle size of the rare earth oxide is 1 to 1.5 μm.
[0062] The alumina ceramic substrate in this embodiment is prepared by the following preparation method, which specifically includes the following steps:
[0063] (1)Ba 0.4 Sr 0.6 Preparation of TiO3 powder
[0064] The pre-synthesized BaTiO3 and SrTiO3 powders were weighed in a molar ratio of 2:3, and wet-milled with water for 5 hours. The mixed powders were dried at 90°C, and then the dried mixture was ground and pressed into a relatively loose block. BaTiO3 was synthesized in a binder removal furnace at 1250°C for 4 hours. 0.4 Sr 0.6 TiO3 powder, after cooling, grind the block into fine powder for later use.
[0065] (2) Ball milling
[0066] Will Ba 0.4 Sr 0.6 TiO3, alumina, MgO, CaO, SiO2, lanthanum oxide, dispersant phosphate (the amount is 0.5-2% of the mass of the ceramic composition), and binder PVB (the amount is 5-10% of the mass of the ceramic composition) are mixed and then ball-milled. The ball-milling solvent is toluene and isopropanol in a volume ratio of 1:1, the ball-milling medium is alumina balls, the mass ratio of powder to alumina balls is 1:1.5, and a mixed slurry is obtained after 18 hours of ball-milling.
[0067] (3)Casting
[0068] The mixed slurry is subjected to vacuum degassing for 6 hours; the vacuum degassing slurry is subjected to tape casting to obtain a green body.
[0069] (4) Sintering
[0070] The green body was left to stand at room temperature for 3 days and then debinded and sintered in a debinding furnace. First, the binder was removed at 300°C for 24 hours to remove the binder in the green body. Then the temperature was raised to 1550°C and maintained for 20 hours to obtain an alumina ceramic substrate.
[0071] Example 2
[0072] The difference between this embodiment and embodiment 1 is that the composition ratio of the ceramic composition is different. The composition ratio of the ceramic composition in this embodiment is as follows:
[0073] composition Alumina <![CDATA[Ba x Sr. 1-x TiO3]]> Glass Phase Rare Earth Oxides Mass percentage 97.2% 1.7% 0.7% 0.4%
[0074] Example 3
[0075] The difference between this embodiment and embodiment 1 is that the composition ratio of the ceramic composition is different. The composition ratio of the ceramic composition in this embodiment is as follows:
[0076] composition Alumina <![CDATA[Ba x Sr. 1-x TiO3]]> Glass Phase Rare Earth Oxides Mass percentage 97.5% 1.5% 0.5% 0.5%
[0077] Example 4
[0078] The difference between this embodiment and embodiment 1 is that the composition ratio of the ceramic composition is different. The composition ratio of the ceramic composition in this embodiment is as follows:
[0079] composition Alumina <![CDATA[Ba x Sr. 1-x TiO3]]> Glass Phase Rare Earth Oxides Mass percentage 98% 1% 0.4% 0.6%
[0080] Example 5
[0081] The difference between this embodiment and embodiment 1 is that the composition ratio of the ceramic composition is different. The composition ratio of the ceramic composition in this embodiment is as follows:
[0082] composition Alumina <![CDATA[Ba x Sr. 1-x TiO3]]> Glass Phase Rare Earth Oxides Mass percentage 99% 0.5% 0.3% 0.2%
[0083] Example 6
[0084] The difference between this embodiment and embodiment 3 is that Ba x Sr 1-x x=0.3 in TiO3.
[0085] Ba in this embodiment 0.3 Sr 0.7 The preparation method of TiO3 is as follows:
[0086] The pre-synthesized BaTiO3 and SrTiO3 powders were weighed in a molar ratio of 3:7, and wet-milled for 6 hours with water as the medium. The mixed powders were dried at 100°C, and then the dried mixture was ground and pressed into a relatively loose block. BaTiO3 was synthesized in a binder removal furnace at 1250°C for 4 hours. 0.3 Sr 0.7 TiO3 powder, after cooling, grind the block into fine powder for later use.
[0087] Example 7
[0088] The difference between this embodiment and embodiment 3 is that Ba x Sr 1-x x=0.5 in TiO3.
[0089] Ba in this embodiment 0.5 Sr 0.5 The preparation method of TiO3 is as follows:
[0090] The pre-synthesized BaTiO3 and SrTiO3 powders were weighed in a 1:1 molar ratio and wet-milled with water for 6 hours. The mixed powders were dried at 100°C, and then the dried mixture was ground and pressed into a relatively loose block. BaTiO3 was synthesized in a binder removal furnace at 1250°C for 4 hours. 0.5 Sr 0.5 TiO3 powder, after cooling, grind the block into fine powder for later use.
[0091] Example 8
[0092] The difference between this embodiment and embodiment 3 is that the mass ratio of MgO:CaO:SiO2 in the glass phase is 1:0.7:2.
[0093] Example 9
[0094] The difference between this embodiment and embodiment 3 is that the mass ratio of MgO:CaO:SiO2 in the glass phase is 1:1.3:2.
[0095] Example 10
[0096] The difference between this embodiment and embodiment 3 is that the mass ratio of MgO:CaO:SiO2 in the glass phase is 1:1:1.6.
[0097] Embodiment 11
[0098] The difference between this embodiment and embodiment 3 is that the mass ratio of MgO:CaO:SiO2 in the glass phase is 1:0.7:2.4.
[0099] Example 12
[0100] The difference between this embodiment and embodiment 1 is that the rare earth oxide is Nd2O3.
[0101] Example 13
[0102] The difference between this embodiment and embodiment 1 is that the rare earth oxide is Dy2O3.
[0103] Embodiment 14
[0104] The difference between this embodiment and embodiment 1 is that the rare earth oxide is CeO2.
[0105] Comparative Example 1
[0106] The difference between this comparative example and Example 1 is that the composition ratio of the ceramic composition is different. The composition ratio of the ceramic composition in this comparative example is as follows:
[0107] composition Alumina <![CDATA[Ba x Sr. 1-x TiO3]]> Glass Phase Rare Earth Oxides Mass percentage 95% 2.8% 0.9% 1.3%
[0108] Comparative Example 2
[0109] The difference between this comparative example and Example 1 is that the composition ratio of the ceramic composition is different. The composition ratio of the ceramic composition in this comparative example is as follows:
[0110] composition Alumina <![CDATA[Ba x Sr. 1-x TiO3]]> Glass Phase Rare Earth Oxides Mass percentage 99.5% 0.3% 0.1% 0.1%
[0111] Comparative Example 3
[0112] The difference between this comparative example and Example 1 is that the composition ratio of the ceramic composition is different. The composition ratio of the ceramic composition in this comparative example is as follows:
[0113] composition Alumina <![CDATA[Ba x Sr. 1-x TiO3]]> Glass Phase Rare Earth Oxides Mass percentage 98.3% 0.3% 0.7% 0.7%
[0114] Comparative Example 4
[0115] The difference between this comparative example and Example 1 is that the composition ratio of the ceramic composition is different. The composition ratio of the ceramic composition in this comparative example is as follows:
[0116] composition Alumina <![CDATA[Ba x Sr. 1-x TiO3]]> Glass Phase Rare Earth Oxides Mass percentage 97% 2.3% 0.3% 0.4%
[0117] Comparative Example 5
[0118] The difference between this comparative example and Example 1 is that the composition ratio of the ceramic composition is different. The composition ratio of the ceramic composition in this comparative example is as follows:
[0119] composition Alumina <![CDATA[Ba x Sr. 1-x TiO3]]> Glass Phase Rare Earth Oxides Mass percentage 97.5% 2% 0.1% 0.4%
[0120] Comparative Example 6
[0121] The difference between this comparative example and Example 1 is that the composition ratio of the ceramic composition is different. The composition ratio of the ceramic composition in this comparative example is as follows:
[0122] composition Alumina <![CDATA[Ba x Sr. 1-x TiO3]]> Glass Phase Rare Earth Oxides Mass percentage 97.5% 1% 0.9% 0.6%
[0123] Comparative Example 7
[0124] The difference between this comparative example and Example 1 is that the composition ratio of the ceramic composition is different. The composition ratio of the ceramic composition in this comparative example is as follows:
[0125] composition Alumina <![CDATA[Ba x Sr. 1-x TiO3]]> Glass Phase Rare Earth Oxides Mass percentage 97.5% 2% 0.5% 0%
[0126] Comparative Example 8
[0127] The difference between this comparative example and Example 1 is that the composition ratio of the ceramic composition is different. The composition ratio of the ceramic composition in this comparative example is as follows:
[0128] composition Alumina <![CDATA[Ba x Sr. 1-x TiO3]]> Glass Phase Rare Earth Oxides Mass percentage 98% 1.4% 0.5% 0.1%
[0129] Comparative Example 9
[0130] The difference between this comparative example and Example 1 is that the composition ratio of the ceramic composition is different. The composition ratio of the ceramic composition in this comparative example is as follows:
[0131] composition Alumina <![CDATA[Ba x Sr. 1-x TiO3]]> Glass Phase Rare Earth Oxides Mass percentage 97.5% 1.5% 0.5% 1%
[0132] Comparative Example 10
[0133] The difference between this comparative example and Example 3 is that Ba x Sr 1-x x=0.2 in TiO3.
[0134] Ba of this comparative example 0.2 Sr 0.8 The preparation method of TiO3 is as follows:
[0135] The pre-synthesized BaTiO3 and SrTiO3 powders were weighed in a molar ratio of 1:4, and wet-milled for 6 hours with water as the medium. The mixed powders were dried at 100°C, and then the dried mixture was ground and pressed into a relatively loose block. BaTiO3 was synthesized in a binder removal furnace at 1250°C for 4 hours. 0.2 Sr 0.8 TiO3 powder, after cooling, grind the block into fine powder for later use.
[0136] Comparative Example 11
[0137] The difference between this comparative example and Example 3 is that Ba x Sr 1-x x=0.6 in TiO3.
[0138] Ba of this comparative example 0.6 Sr 0.4 The preparation method of TiO3 is as follows:
[0139] The pre-synthesized BaTiO3 and SrTiO3 powders were weighed in a molar ratio of 3:2, and wet-milled with water for 6 hours. The mixed powders were dried at 100°C, and then the dried mixture was ground and pressed into a relatively loose block. BaTiO3 was synthesized in a debinding furnace at 1250°C for 4 hours. 0.6 Sr 0.4 TiO3 powder, after cooling, grind the block into fine powder for later use.
[0140] Comparative Example 12
[0141] The difference between this comparative example and Example 3 is that the mass ratio of MgO:CaO:SiO2 in the glass phase is 1:0.5:2.
[0142] Comparative Example 13
[0143] The difference between this comparative example and Example 3 is that the mass ratio of MgO:CaO:SiO2 in the glass phase is 1:1.5:2.
[0144] Comparative Example 14
[0145] The difference between this comparative example and Example 3 is that the mass ratio of MgO:CaO:SiO2 in the glass phase is 1:1:1.
[0146] Comparative Example 15
[0147] The difference between this comparative example and Example 3 is that the mass ratio of MgO:CaO:SiO2 in the glass phase is 1:1:3.
[0148] Comparative Example 16
[0149] The difference between this comparative example and Example 1 is that the composition ratio of the ceramic composition is different. The composition ratio of the ceramic composition in this comparative example is as follows:
[0150] composition Alumina <![CDATA[Ba x Sr. 1-x TiO3]]> Glass Phase Rare Earth Oxides Mass percentage 99% 0% 0.3% 0.7%
[0151] Performance Testing
[0152] The ceramic substrates prepared in Examples 1 to 14 and Comparative Examples 1 to 16 were subjected to the tests listed in Table 1.
[0153] Table 1 Performance test of ceramic substrates of Examples 1 to 14 and Comparative Examples 1 to 16
[0154]
[0155]
[0156] The performance test results of the ceramic substrates of Examples 1 to 14 and Comparative Examples 1 to 16 are shown in Table 2.
[0157] Table 2 Performance test results of ceramic substrates of Examples 1 to 14 and Comparative Examples 1 to 16
[0158]
[0159]
[0160] It can be seen from the above embodiments and comparative examples that:
[0161] Ba of Examples 1-5 x Sr 1-x The amount of TiO3 added gradually decreases, and the dielectric constant and breakdown strength of the ceramic substrate increase with the increase of Ba x Sr 1-xThe increase in the amount of TiO3 added showed a trend of first increasing and then decreasing. The specific performance data further verified that when Ba x Sr 1-x The mass percentage of TiO3 is 1.2-1.7%, and the performance of the entire ceramic substrate is the best.
[0162] It can be seen from the examples and comparative examples 1-4 that when the addition amount is low (the addition amount of comparative examples 2 and 3 is 0.3%), the density, dielectric properties and breakdown strength of the ceramic substrate will decrease. When the addition amount exceeds 2% (the addition amount of comparative example 1 is 2.8%, and the addition amount of comparative example 4 is 2.3%), due to Ba x Sr 1-x TiO3 reacts with alumina to produce more second phases, and the overall dielectric constant of the ceramic decreases.
[0163] It can be seen from the examples and comparative examples 5-6 and 12-15 that by selecting an appropriate amount and range of glass phase addition, a ceramic substrate with good dielectric properties can be obtained. When the addition amount is small (the addition amount in comparative example 5 is 0.1%), it cannot effectively form a liquid phase with alumina ceramics and thus cannot effectively reduce the porosity of the ceramics. The density is large and the density is small. When the addition amount is large (the addition amount in comparative example 6 is 0.9%), Ba x Sr 1-x The reduced content of TiO3 and rare earth oxides cannot effectively promote the liquid phase formation process between them and alumina ceramics, thereby failing to reduce the sintering temperature, resulting in a decrease in the performance of the entire substrate.
[0164] It can be seen from the examples and comparative examples 7-9 that when the rare earth oxide is added in too little or not added, it cannot effectively promote the glass phase and other components to form a low melting point liquid phase, thereby failing to effectively reduce the melting point of the ceramic substrate material; when the addition amount is too high, it exists in large quantities on the grain boundaries of the alumina ceramic, seriously hindering the migration rate of the grain boundaries and being unfavorable for the formation of a dense structure. The density of the ceramic substrate decreases.
[0165] According to the examples and comparative examples 10-11, when Ba x Sr 1-x The x in TiO3 is 0.3-0.5. Since the ratio of Ba and Sr is appropriate, it can well compensate for the defects of the alumina ceramic substrate during sintering, so the dielectric properties, density and breakdown strength of the ceramic substrate are good.
[0166] It can be seen from the examples and comparative example 16 that without adding Ba x Sr 1-x The ceramic substrate made of TiO3 ceramic material has high dielectric properties, high breakdown strength and relatively low density.
[0167] After being made into a ceramic substrate, the ceramic composition provided by the present invention has the advantages of high dielectric constant, low dielectric loss, high breakdown strength and high density, and is widely used in electronic devices, especially high-frequency electronic devices.
Claims
1. A ceramic composition, characterized in that It includes the following components by mass percentage: 97~99% alumina, 0.5~2% Ba x Sr 1-x TiO3, 0.3~0.7% glass phase, 0.2~0.7% rare earth oxide; wherein x=0.3~0.5; the glass phase comprises MgO, CaO and SiO2; the rare earth oxide comprises at least one of lanthanum oxide, neodymium oxide, dysprosium oxide, cerium oxide, yttrium oxide or erbium oxide; in the glass phase, the mass ratio of MgO to CaO is 1:(0.7~1.3), and the mass ratio of MgO to SiO2 is 1:(1.6~2.4).
2. The ceramic composition according to claim 1, characterized in that: The average particle size of the rare earth oxide is 0.5-2 μm.
3. The ceramic composition according to any one of claims 1 to 2, characterized in that It includes the following components in mass percentage: 97.1~98.5% alumina, 0.8~1.9% Ba x Sr 1-x TiO3, 0.35~0.65% glass phase, 0.25~0.65% rare earth oxides.
4. A ceramic substrate, characterized in that: A ceramic composition comprising any one of claims 1 to 3.
5. The method for preparing the ceramic substrate according to claim 4, characterized in that: The following steps are involved: Alumina, Ba x Sr 1- x TiO3, MgO, CaO, SiO2, rare earth oxide, dispersant and binder are mixed, cast and sintered to obtain the ceramic substrate.
6. The preparation method according to claim 5, characterized in that: The dispersant includes at least one of oleic acid, triolein, fish oil or phosphate ester; And / or, the binder includes at least one of polyvinyl butyral, acrylic resin, methyl cellulose, ethyl cellulose, nitrocellulose ester, polyurethane resin or phenolic resin.
7. The preparation method according to claim 5, characterized in that: The sintering temperature is 1400-1800°C.
8. Use of a ceramic composition or a ceramic substrate in an electronic device, characterized in that: The ceramic composition is the ceramic composition according to any one of claims 1 to 3, and the ceramic substrate is the ceramic substrate according to claim 4.
Citation Information
Patent Citations
High-temperature low-loss barium strontium titanate-based energy-storage ceramic and preparation method thereof
CN104725036A
Alumina ceramic substrate and preparation method and application thereof
CN114804840A
Alumina ceramics for dielectric material and production thereof
JP1994293558A